The socioeconomic gradient of alcohol use: an analysis of nationally representative survey data from 55 low-income and middle-income countries - Yuanwei Xu; Pascal Geldsetzer; Jen Manne-Goehler; Michaela Theilmann; Maja-E Marcus; Zhaxybay Zhumadilov; Sarah Quesnel-Crooks; Omar Mwalim; Sahar Saeedi Moghaddam; Sogol Koolaji; Khem B Karki; Farshad Farzadfar; et al. (My University, 2022)
Background: Alcohol is a leading risk factor for over 200 conditions and an important contributor to socioeconomic health inequalities. However, little is known about the associations between individuals' socioeconomic circumstances and alcohol consumption, especially heavy episodic drinking (HED; ≥5 drinks on one occasion) in low-income or middle-income countries. We investigated the association between individual and household level socioeconomic status, and alcohol drinking habits in these settings. Methods: In this pooled analysis of individual-level data, we used available nationally representative surveys-mainly WHO Stepwise Approach to Surveillance surveys-conducted in 55 low-income and middle-income countries between 2005 and 2017 reporting on alcohol use. Surveys from participants aged 15 years or older were included. Logistic regression models controlling for age, country, and survey year stratified by sex and country income groups were used to investigate associations between two indicators of socioeconomic status (individual educational attainment and household wealth) and alcohol use (current drinking and HED amongst current drinkers). Findings: Surveys from 336 287 participants were included in the analysis. Among males, the highest prevalence of both current drinking and HED was found in lower-middle-income countries (L-MICs; current drinking 49·9% [95% CI 48·7-51·2] and HED 63·3% [61·0-65·7]). Among females, the prevalence of current drinking was highest in upper-middle-income countries (U-MIC; 29·5% [26·1-33·2]), and the prevalence of HED was highest in low-income countries (LICs; 36·8% [33·6-40·2]). Clear gradients in the prevalence of current drinking were observed across all country income groups, with a higher prevalence among participants with high socioeconomic status. However, in U-MICs, current drinkers with low socioeconomic status were more likely to engage in HED than participants with high socioeconomic status; the opposite was observed in LICs, and no association between socioeconomic status and HED was found in L-MICs. Interpretation: The findings call for urgent alcohol control policies and interventions in LICs and L-MICs to reduce harmful HED. Moreover, alcohol control policies need to be targeted at socially disadvantaged groups in U-MICs. Funding: Deutsche Forschungsgemeinschaft and the National Center for Advancing Translational Sciences of the US National Institutes of Health.